PERBEDAAN METODE KOMUNIKASI PERTANIAN YANG DIBERIKAN TERHADAP PENGETAHUAN DAN KETERAMPILAN PETANI DALAM PENERAPAN TEKNOLOGI PERTANIAN DI DESA TELUK DAWAN KABUPATEN TANJUNG JABUNG TIMUR - Wiwin Alawiyah (Universitas Batanghari Jambi, 2016)
This research was conducted in Teluk Dawan village, East Tanjung Jabung District. The aim of this research was to know the farmer’s knowledge and skill of agricuture tecnology application. Beside the other aim was to analize the deferences of each variable on the deferent extention methode. Description methode which completed by simple random sampling (there were 30 respondents from 218 populations). The result of the research showed that the farmer’s knowledge score who used the “group extention methode” (87,00% from the ideal score) was higher than that who used the “visited extention method” (85,20% from the ideal score). The farmer’s skill score who used the “group extention methode” (84,00% from the ideal score) was lower than that who used the “visited extention method” (86,20% from the ideal score). Key words : Extention Method, Knowledge and Skill, agriculture technology